2006
DOI: 10.1167/iovs.05-1452
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Anti-Angiogenic Probes of the Ubiquitin Proteasome Pathway: Potential Application to Choroidal Neovascularization

Abstract: HCECs share with HUVECs a similar response to UPP inhibitors, suggesting that this well-conserved pathway that regulates angioinflammatory mechanisms could be exploited for drug-targeting in the development of novel agents for CNV treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…Importantly, corneal angiogenesis was also simultaneously inhibited with 2 mg/kg of WFA in this chemical injury model, and without adverse effects on corneal resurfacing of denuded epithelium or on pre-existing limbal vasculature (10). Furthermore, we show that measurable levels of WFA (3 ng/l) in serum are achieved 6 h after a single 10 mg/kg intraperitoneal injection (supplemental data); the 2 mg/kg dose of WFA thus provides a systemic anti-inflammatory dose sufficient to down-regulate transcription factor NF-B activation (18,54,55). This posit is consistent with our previous finding that production of the potent inflammatory mediator TNF-␣ (56) is also blocked in vivo at this WFA dose (18).…”
Section: Discussionmentioning
confidence: 64%
“…Importantly, corneal angiogenesis was also simultaneously inhibited with 2 mg/kg of WFA in this chemical injury model, and without adverse effects on corneal resurfacing of denuded epithelium or on pre-existing limbal vasculature (10). Furthermore, we show that measurable levels of WFA (3 ng/l) in serum are achieved 6 h after a single 10 mg/kg intraperitoneal injection (supplemental data); the 2 mg/kg dose of WFA thus provides a systemic anti-inflammatory dose sufficient to down-regulate transcription factor NF-B activation (18,54,55). This posit is consistent with our previous finding that production of the potent inflammatory mediator TNF-␣ (56) is also blocked in vivo at this WFA dose (18).…”
Section: Discussionmentioning
confidence: 64%
“…41) Recent studies have reported that UCH-L1 exhibited anti-angiogenesis activity by affecting the development of choroidal new vessels in age-related macular degeneration disease. 42,43) Our previous experiments have shown that the expression of UCH-L1 in the retinopathy of diabetic rats was significantly lower than that of control rats by the proteomic technique. Treating with GSPE significantly increased the expression of UCH-L1 in diabetic rats.…”
Section: Fig 2 Effects Of Gspb2 On the Cell Migration Of Age-stimulmentioning
confidence: 98%
“…), thus the methyl ketal 255 is probably formed during isolation. Nicotra et al reported the isomeric clorohydrin, jaborosalactone 37 (256), from Jaborosa rotacea (120). Interestingly, the D 2 -withanolide 257 was present in Jaborosa caulescens var.…”
Section: Withametelins and Sativolidesmentioning
confidence: 99%
“…Withaferin A and withanolide D (508) also displayed antiangiogenic activity in human choroidal endothelial cells (HCECs). These results may lead to novel treatments of choroidal neovascularization, the major contributor to age-related macular degeneration and one of the leading causes of irreversible blindness in the Western hemisphere (256). Physalin B (463) has been identified recently as an inhibitor of the ubiquitin-mediated proteasome pathway in the DLD-1 human colon cancer cell line, producing an accumulation of ubiquitinated proteins and inhibiting TNFa-induced NF-kB activation (257).…”
Section: Antiangiogenic Activitymentioning
confidence: 99%